Analisis Pemenuhan Kebutuhan Masyarakat di Rantau Panjang Estate dengan Menggunakan Kredit dalam Perspektif Ekonomi Islam - Meirza Ayu Humairoh; Hilda Hilda (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The use of credit by the public is generally driven by the need and desire to meet certain requirements that cannot be fulfilled with cash. Credit makes it easier for people to meet their various needs, especially for those who do not have enough funds at the time. However, in practice, there are often obstacles such as payment delays, breaches of agreed-upon deadlines, and discrepancies in the recording of installment payments. These issues can create problems for both the creditor and the debtor. This study aims to examine the use of the credit concept by the community and analyze how credit helps fulfill the needs of the community. The study uses a qualitative method with a descriptive research approach. Data collection was done through observation, interviews, and document gathering. The collected data were then analyzed by presenting the data and drawing conclusions. The results of the study show that the use of the credit concept by the community in Rantau Panjang Estate to meet their needs has fulfilled the conditions of a muamalah agreement in accordance with the principles of buying and selling. First, the people involved in the transaction, namely the seller and the buyer, must meet the requirements of being rational, consenting freely, and agreeing mutually. Second, the agreement between the seller and the buyer must include the price and the payment period that both parties have agreed upon. Third, the object or goods being sold must have utility and be clearly defined in terms of its nature, size, and type. Fourth, the price must be clear, with the credit price being higher than the cash price. Additionally, the use of credit by the community in Rantau Panjang Estate has also applied the principles of the Islamic market mechanism, such as Ar-Ridha (mutual consent), healthy competition, honesty, transparency, and justice. This indicates that the credit transactions conducted are in accordance with the rules of Islam and can serve as a fair model for all parties involved.